Impact of Flap Size and Comorbidities on Supraclavicular Artery Island Flap Outcomes - William Ruffin; Thomas J. Gal (OTO Open, 2024)
Abstract Objective Use of the supraclavicular artery island flap (SCAIF) in head and neck reconstruction has increased in recent years. Limited but improving experience among reconstructive surgeons with the procedure have exposed numerous issues associated with flap success. The objective of this study is to examine the role of flap size on viability. Study Design Retrospective case series. Setting Tertiary Academic Medical Center. Methods Review of patients undergoing SCAIF reconstruction between January 2014 and March 2022 was performed. Flap failure was defined as >50% skin paddle loss. The total flap surface area was examined. Multivariable analysis was performed to evaluate the association of other variables associated with flap failure. Results Eighty‐nine supraclavicular island flaps were reviewed. Mean patient age was 63.2 ± 11.4 years. Fifty‐five (61.2%) were male. Forty‐five flaps (50.6%) were used for the reconstruction of defects of the skin of the neck/face. Twenty‐nine flaps (32.6%) were utilized for defects of the pharynx/oropharynx, and 15 (16.9%) were utilized for oral cavity defects. Flap success rate was 94% (73/89). Flap site was not associated with flap failure (P = .46). Flaps >25 cm2 were 75% more likely to be successful. Multivariable logistic regression to assess the association of flap size in the context of other co‐morbidities indicated flaps >25 cm2 were 3.6 times more likely to succeed regardless of co‐morbidities, and patients with chronic obstructive pulmonary disease (COPD) have a 7‐fold risk of flap failure (odds ratio: 7.3, 1.72‐30.98, P = .007). Conclusion An association with improved flap outcomes and larger skin paddles was observed in this series. The applicability of these observations to smaller flaps and larger series with more surgeons requires further study. Co‐morbidities, particularly, COPD, continue to impact flap outcomes.